Bacterial Cadmium-Immobilization Activity Measured by Isothermal Microcalorimetry in Cacao-Growing Soils From Colombia - Bravo, Daniel (Frontiers in Environmental Science, 2022)
In cacao farms, the presence of cadmium (Cd) is a major issue for commercialization, particularly for countries such as Colombia. Cadmium-tolerant bacteria (CdtB) are an important functional group of microorganisms with a potential for bioremediation strategies. Cd immobilization activity by CdtB can be accurately measured by isothermal microcalorimetry (IMC). In this study, the metabolic capacity of an entire CdtB community in cacao farm soils from three cacao-producing districts of Colombia, with and without the addition of Cd was measured using IMC. The differences between the observed peaks in metabolic activity related to Cd immobilization were analysed to determine whether activation of CdtB populations occurred when Cd content was increased. The thermograms from Santander soil samples have a major metabolic activity of the CdtB community compared to peaks of maximal heat-flow in the samples from Antioquia and Arauca. IMC showed differences in Cd immobilization ratios of the soil samples of 0.11 - 0.30 mg kg-1 h-1 at 25oC over 12 days of thermal monitoring. Furthermore, the amplicons of cadA and smt genes from the soil samples allow elucidation of possible metabolic mechanisms used by CdtB soil populations. The gene amplification confirmed the existence of CdtB populations related to both bioweathering and biochelating metabolic capacities. Scanning electron microscope (SEM) images supported the existence of otavite biologically induced by CdtB naturally. A Pearson correlation analysis was made between kinetical growth parameters and thermodynamic data. Besides, a PCA was performed between CdtB cadA gene copies, soil pH and SOM indicating the effect of CdtB in Cd translocation. Thus, it is concluded that the combination of Cd immobilization ratios obtained using isothermal microcalorimetry, the molecular basis of metabolic immobilization, and SEM imagery could act as a useful toolkit to identify CdtB populations for bioremediation strategies in contaminated cacao farms. The research importance of this study is the use of combined tools for quantitative IMC measurements to identify and assess Cd metabolic capacities of CdtB populations in soil, in situ, as a new proxy for CdtB assessment in cacao-growing soils.